2019
DOI: 10.1093/jas/skz080
|View full text |Cite
|
Sign up to set email alerts
|

RAPID COMMUNICATION: Residual feed intake in beef cattle is associated with differences in protein turnover and nutrient transporters in ruminal epithelium

Abstract: Residual feed intake (RFI) is a widely used measure of feed efficiency in cattle. Although the precise biologic mechanisms associated with improved feed efficiency are not well-known, most-efficient steers (i.e., with low RFI coefficient) downregulate abundance of proteins controlling protein degradation in skeletal muscle. Whether cellular mechanisms controlling protein turnover in ruminal tissue differ by RFI classification is unknown. The aim was to investigate associations between RFI and signaling through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 36 publications
1
11
0
1
Order By: Relevance
“…The difference between the species in respect of SGOT levels in two feed efficiency subgroups of buffalo heifers may be attributed to the difference in rumen microbiota and functioning of liver of both species ( 50 ). Efficient heifer calves also tended to have a lower concentration of T 3 during the performance evaluation ( p < 0.05), compared to the efficient heifer calves as reported earlier ( 23 ). It is also documented that during growth, T3 has a synergistic relationship with the growth hormone in heifers ( 51 ), supporting the argument of metabolic rate differences between heifer calves of distinct feed efficiency classifications.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…The difference between the species in respect of SGOT levels in two feed efficiency subgroups of buffalo heifers may be attributed to the difference in rumen microbiota and functioning of liver of both species ( 50 ). Efficient heifer calves also tended to have a lower concentration of T 3 during the performance evaluation ( p < 0.05), compared to the efficient heifer calves as reported earlier ( 23 ). It is also documented that during growth, T3 has a synergistic relationship with the growth hormone in heifers ( 51 ), supporting the argument of metabolic rate differences between heifer calves of distinct feed efficiency classifications.…”
Section: Resultssupporting
confidence: 70%
“…An insight into the relationship of various blood parameters with ADG with FCE can shed light on physiological dynamics underlying the metabolic changes, using machine learning approaches ( 20 22 ). The biological closeness between feed efficiency and the animal's ability to convert feed nitrogen ( N ) into animal protein, i.e., N-use efficiency or N partitioning and protein turnover across individuals ( 23 ), has been used for predicting RFI in growing cattle due to the difference in rates of amino acid transamination ( 24 ).…”
Section: Introductionmentioning
confidence: 99%
“…Similar studies looking at this ratio in urine from beef cattle did not, however, find any difference and concluded that the muscle degradation rate was similar across RFI groups 18 , 33 . In contrast, evidence of lower protein turnover rate in efficient RFI animals have been reported in cattle 34 , 35 and swine 36 using indirect molecular approaches. Similarly, Carvalho et al 37 found greater muscle abundance of Heat Shock Protein 1 (HSPB1) in skeletal muscle for Low- than High-RFI animals and suggested this difference may account for an increased actin and myosin degradation and protein breakdown, and therefore greater protein turnover in skeletal muscle of less efficient animals.…”
Section: Discussionmentioning
confidence: 87%
“…Protein turnover and tissue metabolism have been reported to account for up to 37% of variation in feed efficiency in beef cattle ( Richardson and Herd, 2004 ). Elolimy et al, 2019 reported an association between residual feed intake and protein turnover and nutrient transporters in ruminal epithelium of beef cattle. In their study, there was a reduced abundance of intracellular enzymes associated with protein degradation and reduced abundance of amino acid transporters in the ruminal epithelium of highly efficient cattle.…”
Section: Discussionmentioning
confidence: 99%